Relationship of obesity with periodontitis among patients attending a dental college in Chennai: A cross-sectional survey - Delfin Lovelina Francis; B Kumara Raja; Chitraa R Chandran (Wolters Kluwer Medknow Publications, 2017)
Introduction: Periodontal disease is a global public health issue, and it has been suggested to be an associated risk factor for obesity. However, the studies addressing these relationships were sparse. Aim: This study aims to determine whether there was a relationship between body mass index (BMI) and periodontal disease. Materials and Methods: This cross-sectional study was carried out on 400 individuals who were randomly selected from the outpatient department of a dental college in Chennai. The community periodontal index (CPI) was used to assess periodontal status. Participants with a CPI score (CPI 0-2) were considered as nonperiodontitis group and those with a CPI score (CPI 3-4) were considered to have periodontitis. Statistical analysis was performed using Chi-square test and logistic regression analysis was used to estimate the association between BMI and periodontitis. P < 0.05 was considered as statistically significant. Results: The prevalence of periodontitis was 29.2% with a mean BMI score of 22.45 ± 05.27. Logistic regression analysis revealed a 30% increased risk for periodontitis per 1-kg/m2 increase in BMI (adjusted odds ratio, 1.30; 95% confidence interval, 1.08-1.27; P < 0.05). Conclusion: Periodontal disease was associated with increased BMI establishing a link between obesity and periodontitis.